2022
DOI: 10.1139/cjps-2021-0039
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity, anastomosis groups, host range, and genetic diversity of Rhizoctonia species isolated from soybean, pea, and other crops in Alberta and Manitoba, Canada

Abstract: Root rot is a common disease in soybean (<i>Glycine max</i>) and field pea (<i>Pisum sativum</i>), which restrain increased production in Canada. Sixty-seven isolates of <i>Rhizoctonia</i> were recovered from various diseased plants in Alberta, Canada along with three isolates from diseased soybean plants in Manitoba, Canada. According to their anastomosis behavior, 23 (32.9%) of the isolates were identified as anastomosis group (AG) 4 (AG4), 7 (10.0%) were AG2-1, 10 (14.3%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Fusarium proliferatum has been reported to cause vascular wilt in chickpeas from Cuba [57]. A recent Canadian study by Yu et al [58] showed that canola and leguminous crops were highly susceptible to F. proliferatum. At the same time, barley and wheat were partially susceptible, indicating a broad host range for this species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fusarium proliferatum has been reported to cause vascular wilt in chickpeas from Cuba [57]. A recent Canadian study by Yu et al [58] showed that canola and leguminous crops were highly susceptible to F. proliferatum. At the same time, barley and wheat were partially susceptible, indicating a broad host range for this species.…”
Section: Discussionmentioning
confidence: 99%
“…Given that F. avenaceum has a broad host range and can infect small grain crops such as barley, wheat, and canola [19,40], alternative non-host crops for this aggressive species must be incorporated into crop rotation programs. Previous studies [50][51][52][53][54][55][56][57][58][59][60][61][62] highlighted the need for identifying sources of resistance to F. oxysporum f. sp. ciceri.…”
Section: Discussionmentioning
confidence: 99%
“…Current classification systems divide individual, multinucleate R. solani strains into 13 different anastomosis groups (AGs), based on hyphal fusion, culture morphology, rDNAinternal transcribed spacer sequences and pathogenicity [80]. Divergent studies revealed that AG 1, AG 2-1, AG 2-2, AG 4, AG 9 and to a lower degree AG 5 are the most aggressive anastomosis groups inducing seedling blight and/or root rot symptoms on flax [28,[81][82][83][84][85][86][87]. Strains belonging to AG 3 only attack older plants, resulting in limited root rot [86], and AG 6 and AG 7 do not appear to be pathogenic [28].…”
Section: Seedling Blight/root Rot-rhizoctonia Solanimentioning
confidence: 99%
“…Strains belonging to AG 3 only attack older plants, resulting in limited root rot [86], and AG 6 and AG 7 do not appear to be pathogenic [28]. The binucleate Rhizoctonia AG-E has also been isolated from older flax plants, which showed typical symptoms of root rot [85].…”
Section: Seedling Blight/root Rot-rhizoctonia Solanimentioning
confidence: 99%
“…These diverse markers were utilized to evaluate and characterize the genetic variability and AGs of R. solani. Among these molecular markers, the sequence analysis of the rDNA ITS1-5.8S-ITS2 region stands out as a particularly potent tool for investigating genetic diversity and phylogenetic relationships within the anastomosis groups (AGs) and AG subgroups of R. solani [25][26][27][28][29][30][31][32][33][34]. The rationale is that all eukaryotic genomes contain these regions, and they are rapidly evolving and are surrounded by nucleotide sequences that are highly conserved.…”
Section: Introductionmentioning
confidence: 99%